2016
DOI: 10.1016/j.celrep.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

RNF166 Determines Recruitment of Adaptor Proteins during Antibacterial Autophagy

Abstract: Summary Xenophagy is a form of selective autophagy that involves the targeting and elimination of intracellular pathogens through several recognition, recruitment, and ubiquitination events. E3 ubiquitin ligases control substrate selectivity in the ubiquitination cascade; however, systematic approaches to map the role of E3 ligases in antibacterial autophagy have been lacking. Here we screened more than 600 putative human E3 ligases, identifying E3 ligases that are required for adaptor protein recruitment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 73 publications
(106 reference statements)
0
59
0
Order By: Relevance
“…Recently, studies identified ubiquitin ligases that depending upon their site of ubiquitination inhibited or facilitated p62’s function (Heath et al, 2016; Jongsma et al, 2016; Pan et al, 2016). The E3 ubiquitin ligase TRIM21 ubiquitylates p62 at lysine 7 within it PB1 domain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies identified ubiquitin ligases that depending upon their site of ubiquitination inhibited or facilitated p62’s function (Heath et al, 2016; Jongsma et al, 2016; Pan et al, 2016). The E3 ubiquitin ligase TRIM21 ubiquitylates p62 at lysine 7 within it PB1 domain.…”
Section: Introductionmentioning
confidence: 99%
“…This ubiquitination event was proposed to enhance p62’s interaction with other ubiquitin adaptors such as, TOLLIP, thus facilitating vesicular cargo sorting (Jongsma et al, 2016). In addition, RNF166 ubiquitinates p62 at residues K91 and K189 (Heath et al, 2016). Interestingly, these events involve atypical ubiquitin chains that are K29- and K33-linked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several E3 ubiquitin ligases including LRSAM1, Parkin, Smurf1, RNF166, and some TRIM proteins have each been shown to ubiquitinate bacteria or bacteria-associated proteins to drive antibacterial autophagy 7376 . Various TRIM proteins have also been implicated in antibacterial autophagy as well as other types of selective autophagy that have a direct effect on inflammation 74, 77, 78 .…”
Section: Autophagy and The Host Response To Bacteriamentioning
confidence: 99%
“…Recent studies have identified a number of proteins that function in mitophagy, antibacterial autophagy, and/or virophagy (autophagic elimination of viruses), suggesting that these processes share signaling components. The E3 ubiquitin ligase Parkin is critical for mitophagy and has recently been shown to be recruited to intracellular M. tuberculosis and S. Typhimurium to promote autophagy 54, 74, 85 . The E3 ligase SMURF1 and the peroxisomal protein PEX13 are also critical for mitophagy, virophagy, and antibacterial autophagy 76, 86, 87 .…”
Section: Cross-regulation Of Selective Autophagy Pathwaysmentioning
confidence: 99%